Association of 5-hydroxymethylation and 5-methylation of DNA cytosine with tissue-specific gene expression. Issue 2 (1st February 2017) - Ponnaluri, V. K. Chaithanya; Ehrlich, Kenneth C.; Zhang, Guoqiang; Lacey, Michelle; Johnston, Douglas; Pradhan, Sriharsa; Ehrlich, Melanie
ABSTRACT: Differentially methylated or hydroxymethylated regions (DMRs) in mammalian DNA are often associated with tissue-specific gene expression but the functional relationships are still being unraveled. To elucidate these relationships, we studied 16 human genes containing myogenic DMRs by analyzing profiles of their epigenetics and transcription and quantitatively assaying 5-hydroxymethylcytosine (5hmC) and 5-methylcytosine (5mC) at specific sites in these genes in skeletal muscle (SkM), myoblasts, heart, brain, and diverse other samples. Although most human promoters have little or no methylation regardless of expression, more than half of the genes that we chose to study—owing to their myogenic DMRs—overlapped tissue-specific alternative or cryptic promoters displaying corresponding tissue-specific differences in histone modifications. The 5mC levels in myoblast DMRs were significantly associated with 5hmC levels in SkM at the same site. Hypermethylated myogenic DMRs within CDH15, a muscle- and cerebellum-specific cell adhesion gene, and PITX3, a homeobox gene, were used for transfection in reporter gene constructs. These intragenic DMRs had bidirectional tissue-specific promoter activity that was silenced by in vivo -like methylation. The CDH15 DMR, which was previously associated with an imprinted maternal germline DMR in mice, had especially strong promoter activity in myogenic host cells. These findings are consistent with the controversial hypothesis that intragenic DNA methylation can facilitate transcription and is not just a passive consequence of it. Our results support varied roles for tissue-specific 5mC- or 5hmC-enrichment in suppressing inappropriate gene expression from cryptic or alternative promoters and in increasing the plasticity of gene expression required for development and rapid responses to tissue stress or damage.